A study to correlate serum anti mullerian hormone, basal follicle stimulating hormone and antral follicle count in primary infertility as a measure of ovarian reserve - Shruthi A; Sujatha Prabhu (Barpeta Obstetrics and Gynaecological Society, 2022)
Objectives: This study aims to find the correlation between anti mullerian hormone (AMH) and follicle stimulating hormone (FSH) and to observe the above mentioned hormones' relation with antral follicle count (AFC) in patients with primary infertility. Methodology: This is a cross-sectional correlation study in which 60 patients with primary infertility meeting inclusion criteria, attending infertility clinic in ESIC MC PGIMSR, Rajajinagar between January 2017 and June 2018 were enrolled by simple random sampling. Detailed menstrual, obstetric, coital and medical history was obtained. On the third day of the spontaneous cycle, all patients were investigated with a transvaginal scan to assess the number of antral follicles and a fasting venous blood sample was obtained for the measurement of serum AMH and serum basal FSH level. Results: Basal serum FSH shows a moderately strong negative correlation with antral follicle count (AFC) (r=0.65; p=<0.001); and a strong negative correlation with anti mullerian hormone (AMH) (r=0.69 and p=<0.001). However, the strongest correlation between a biochemical marker and biophysical marker of ovarian reserve is between anti mullerian hormone (AMH) and antral follicle count (AFC) with a very strong positive correlation with a correlation co-efficient r=0.89 (p=<0.001). Conclusion: Serum AMH best correlates with the antral follicle count. Antral follicle counts although an efficient test to detect ovarian reserve is uncomfortable for the patient as it has to be done during menstrual flow. Serum AMH with minimal intracycle and intercycle variation is a more convenient marker to assess ovarian reserve while it maintains the accuracy of AFC.